Predictive Value of Soluble Growth Stimulator Gene 2 Protein for Coronary Slow Flow/No-Reflow in ST-Elevation Myocardial Infarction Patients Receiving Percutaneous Coronary Intervention - Shu-min Chang; Yan-tan Yu; Bo Luan; Ai-jie Hou; Yong Wang (Journal of Interventional Cardiology)
Background. Soluble growth stimulator gene 2 protein (sST2) is associated with heart failure and myocardial infarction; however, the predictive value of plasma sST2 level for coronary slow flow/no-reflow (CSF/NRF) is unclear. This study aimed to explore the predictive value of plasma sST2 levels for CSF/NRF in patients with ST-elevation myocardial infarction (STEMI) who underwent emergency percutaneous coronary intervention (PCI). Methods. A total of 242 STEMI patients who underwent emergency PCI at our hospital between November 2020 and July 2021 were enrolled in this study. According to the postprocedural procedure, these patients were divided into the CSF/NRF and control groups. Clinical data were collected from both groups and were used to explore the predictive value of serum sST2 levels for CSF/NRF. Results. Of the total 242 patients, CSF/NRF was observed in 50 patients (20.7%). Statistically significant differences (P<0.05) were observed in age, diabetes mellitus, sST2 level, neutrophil-to-lymphocyte ratio (NLR), fasting blood sugar, preprocedural blood pressure, intraprocedural hypotension, N-terminal pro-B-type natriuretic peptide, MB isoenzyme of creatine kinase (CK-MB), and cardiac troponin I (cTNI). Multivariate analysis showed that the sST2 level, NLR, and intraoperative hypotension were independent risk factors for CSF/NRF. ROC curve analysis showed that the sensitivity and specificity of the sST2 level for predicting CSF/NRF were 68.0% and 75.5%, respectively, when the sST2 level was more than 64.6 ng/mL (AUC = 0.780, 95% CI: 1.003–1.020, P=0.009). Conclusion. For STEMI patients, preprocedural sST2 levels significantly correlated with CSF/NRF occurring in PCI. sST2 level is a potential predictor for CSF/NRF occurrence.